Analisis Pemecahan Masalah Matematika Sistem Persamaan Linear Dua Variabel Berdasarkan Pemrosesan Informasi Auditori Siswa - Danial, Danial; Arafah, Andi Asrafiani (Hybrid: Jurnal Pendidikan dan Pembelajaran Sains, 2025)
This study aims to analyze students’ mathematical problem-solving processes in the topic of linear equations in two variables (SPLDV) based on auditory information processing. A qualitative descriptive approach was employed, with data collected through problem-solving tests and in-depth interviews. The research subjects were selected based on their dominant auditory learning style. The findings reveal that students with auditory tendencies undergo a systematic information-processing sequence, beginning with understanding the problem through reading aloud, organizing information, planning strategies, and evaluating the results. Verbal activities such as self-talk and verbal repetition help maintain focus, strengthen memory, and enhance conceptual understanding of SPLDV procedures. Furthermore, students demonstrate cognitive flexibility by applying various solution methods, reflecting their reflective and metacognitive abilities. Overall, the study confirms that auditory information processing plays an essential role in improving mathematical problem-solving skills. Therefore, teachers are encouraged to integrate auditory based learning strategies, such as verbal explanations, discussions, and reflective speaking to support students’ comprehension and strengthen their metacognitive and numerical literacy skills in mathematics learning.